Organizational behavior and management - Ivancevich, John M. (McGraw-Hill Irwin, 2011)
The authors' goal in writing Organizational Behavior and Management 9e is to improve students' ability to understand, interpret, and predict the behavior of people working in organizations. The book combines text, self-learning exercises, group participation exercises, and cases in an integrated way designed to enhance learning and retention of organizational behavior concepts and skills. A solid research base and an appendix on research techniques make this book suitable for a graduate studies course.